C- mac videolaryngoscope: an aide to new findings in Goldenhar Syndrome - Jain, Swati; Kakkar, Mahak (Indian Journal of Case Reports, 2019)
Goldenhar Syndrome (GS) is a congenital disorder with male predominance and sporadic occurrence. Various anomalies are seen in these patients involving almost all systems. The anesthesiologist usually finds difficulty in the airway of these patients as a spectrum of anomalies is seen. We report a new finding in the airway of Goldenhar syndrome with the help of a C-Mac videolaryngoscope, with the base of tongue and uvula being bifid and causing inability to intubate in an 11-year-old girl.